Polyurethane one-component foam formulation optimization for low free isocianate monomer content. (March 2017) - Marques, Ana C; Dias, Helena; Matos, Sandro; Sargaço, Bruno; Simoes, Ricardo; De Schrijver, Aster; Bordado, João C
Recent changes in legislation have forced one-component foam producers to drop the amount of free monomeric isocyanate in their polyurethane systems. Also, it is required that commercial polyurethane aerosol cans exhibit at least one year of shelf life and polyurethane foams must be classified as B2 on the fire testing following DIN 4102. This paper reports on a systematic optimization study of polyurethane formulations dedicated to address these current industry requirements. A one-component foam system exhibiting simultaneously all of these parameters was achieved by reacting conventional diols, a relatively low-molecular weight monol (2-ethylhexanol), a flame retardant high-molecular weight monol (tris(bromoneopentyl)alcohol), a methylene diphenyl diisocyanate-based prepolymer (GreenAdduct 13), and a small amount of 2, 4′-toluene diisocyanate. The use of monols allows producing prepolymers with low free methylene diphenyl diisocyanate by preventing chain extension and, therefore, avoiding extreme viscosity build-up. Toluene diisocyanate also promotes a lower viscosity inside the aerosol can, which enables the use of high enough quantities of high-molecular weight flame retardant monol to achieve a B2 fire test classification.